2019
DOI: 10.1149/2.0151906jes
|View full text |Cite
|
Sign up to set email alerts
|

Slurry-Coated Sheet-Style Sn-PAN Anodes for All-Solid-State Li-Ion Batteries

Abstract: High capacity all-solid-state Li-ion battery anodes were prepared using an industrially scalable solution coating process. Employing commercially available polyacrylonitrile as a mixed conducting binder, we have demonstrated stable cycling, high capacity electrodes with large mass loadings of tin active material. This is, to our knowledge, the first time a high capacity lithium-alloying material has been utilized in a slurry-coated sheet-style all-solid-state Li-ion battery anode. Optimization of this new elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The cathode composite com-posed of COF-TRO/argyrodite SE/acetylene black in a weight ratio of 5:4:1 was conveniently prepared through a facile dry process without using any solvents, which would be beneficial for practical applications and large-scale productions. [6] The rate performance of COF-TRO was evaluated at discharge rates of 0.1, 0.2, 0.5, 1, 2 C, as shown in Figure 4 b, c. A high discharge capacity of 268 mAh g À1 was achieved at 0.1 C, corresponding to 6 Li + insertion/extraction per truxenone moiety, which is consistent with our theoretical prediction. To the best of our knowledge, this is the highest capacity of COF materials reported as cathodes for all-solid-state LIBs so far.…”
Section: Angewandte Chemiesupporting
confidence: 86%
See 1 more Smart Citation
“…The cathode composite com-posed of COF-TRO/argyrodite SE/acetylene black in a weight ratio of 5:4:1 was conveniently prepared through a facile dry process without using any solvents, which would be beneficial for practical applications and large-scale productions. [6] The rate performance of COF-TRO was evaluated at discharge rates of 0.1, 0.2, 0.5, 1, 2 C, as shown in Figure 4 b, c. A high discharge capacity of 268 mAh g À1 was achieved at 0.1 C, corresponding to 6 Li + insertion/extraction per truxenone moiety, which is consistent with our theoretical prediction. To the best of our knowledge, this is the highest capacity of COF materials reported as cathodes for all-solid-state LIBs so far.…”
Section: Angewandte Chemiesupporting
confidence: 86%
“…[1][2][3] All-solid-state lithium ion batteries (LIBs) have been recognized as one of the ideal choices given their safety and long-term stability compared with conventional LIBs using liquid electrolytes. [4][5][6] One of the primary obstacles hindering the capability of current LIBs has been the inferior performance of cathode materials. [7] Inorganic electrodes, particularly transition metal oxides-based materials, such as LiCoO 2 , LiMn 2 O 4 , LiFePO 4 , have been commonly used.…”
mentioning
confidence: 99%
“…[14,22,23] To integrate SEs into large-scale ASLBs for mass production, sheet-type electrodes and SE films are required. [24][25][26][27][28][29][30][31][32][33] For this, it is necessary to use soft polymeric binders to avoid delamination and to supplement the brittleness of the inorganic components of the electrode active materials and SEs. [34][35][36] Moreover, stresses generated by volumetric strains in electrode active materials upon repeated cycling can be buffered by the polymeric binders.…”
mentioning
confidence: 99%
“…Some research studies of the Sn anodes in a bulky form have also been reported. Polyacrylonitrile (PAN) was mixed with Sn nanoparticles as a conducting binder (Dunlap et al, 2019). The loading amount of the PAN binder was optimized (5 wt.%), the discharge capacity of 900 mAh g −1 was obtained for the first cycle, and 643 mAh g −1 was still maintained after 100 cycles at 0.1 C (Dunlap et al, 2019).…”
Section: High-capacity Anodes With Powder Morphology In the All-solid-state Lithium Ion Batteriesmentioning
confidence: 99%
“…Polyacrylonitrile (PAN) was mixed with Sn nanoparticles as a conducting binder (Dunlap et al, 2019). The loading amount of the PAN binder was optimized (5 wt.%), the discharge capacity of 900 mAh g −1 was obtained for the first cycle, and 643 mAh g −1 was still maintained after 100 cycles at 0.1 C (Dunlap et al, 2019). It can be considered that Sn particles were electrochemically linked to the solid electrolyte particles and the current collector during cycling, whose rigid matrix contributed to the stable cycling (Dunlap et al, 2019).…”
Section: High-capacity Anodes With Powder Morphology In the All-solid-state Lithium Ion Batteriesmentioning
confidence: 99%